Traumatic Optic Neuropathy - Miller, Neil R. (Journal of Neurological Surgery Part B: Skull Base, 2021)
A host of different types of direct and indirect, primary and secondary injuries can affect different portions of the optic nerve(s). Thus, in the setting of penetrating as well as nonpenetrating head or facial trauma, a high index of suspicion should be maintained for the possibility of the presence of traumatic optic neuropathy (TON). TON is a clinical diagnosis, with imaging frequently adding clarification to the full nature/extent of the lesion(s) in question. Each pattern of injury carries its own unique prognosis and theoretical best treatment; however, the optimum management of patients with TON remains unclear. Indeed, further research is desperately needed to better understand TON. Observation, steroids, surgical measures, or a combination of these are current cornerstones of management, but statistically significant evidence supporting any particular approach for TON is absent in the literature. Nevertheless, it is likely that novel management strategies will emerge as more is understood about the converging pathways of various secondary and tertiary mechanisms of cell injury and death at play in TON. In the meantime, given our current deficiencies in knowledge regarding how to best manage TON, “primum non nocere” (first do no harm) is of utmost importance.
Keywords: optic neuropathy; trauma; traumatic optic neuropathy; steroids; optic canal decompression